Eight years of Doha trade talks: Where do we stand? - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2009)
We commit ourselves to comprehensive negotiations aimed at: substantial improvements in market access; reductions of, with a view to phasing out, all forms of export subsidies; and substantial reductions in trade-distorting domestic support. We agree that special and differential treatment for developing countries shall be an integral part of all elements of the negotiations….” —Declaration from the World Trade Organization Ministerial Conference in Doha, Qatar, November 14, 2001 When this declaration was adopted eight years ago, there seemed to be a great deal of enthusiasm about this highly ambitious program. Today the mood has changed, and while concluding the negotiations may still be an achievable goal, it is clouded with uncertainty.